Genetic Parameters and Sire Ranking for the Adjusted Estimate of Mozzarella Cheese Production in Italian Mediterranean Buffalo - Parlato, E.; Zicarelli, L. (Journal of Buffalo Science, 2015)
The objectives of this study were to investigate the effect of adjusting mozzarella cheese production (APKM) compare to the unadjusted PKM on genetic parameters and sire ranking in Italian buffalo. 337,158 lactation records at 270d, from years 1997 to 2014, up to fifth parity, of 136,525 animals were analyzed. Estimated Breeding Values (EBVs) for APKM and PKM were predicted by BLUP-Animal Model with the fixed effects of age-parity, days-open, and contemporary-group; and the random factors of animal, permanent environmental and residuals. APKM showed lower heritability (0.23) than that of PKM (0.31) which might be due to the lower genetic correlation between APKM and milk yield (MY) (0.09) compared to that of PKM with MY (0.25). APKM positively changed sire ranking with increasing rank of sire with positive EBVs of Protein and Fat percentage, and decreasing rank of sire with negative EBVs of Protein and Fat percentage. Due to the larger correlation between PKM and MY, by selecting through the PKM, one risk is to increasing the number of buffalo that produce more milk, not optimal for making mozzarella cheese. Whereas, genetic selection through the APKM will increase the number of high-yielding buffalo with positive EBVs for Protein and Fat percentage